1977
DOI: 10.1159/000122717
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Inhibitory Dopaminergic and Stimulatory Noradrenergic Hypothalamic Influence on PMS-Induced Ovulation in the Immature Rat. II. A Pharmacological Analysis

Abstract: Pregnant mare’s serum gonadotropin (PMS; 10 IU day 3O)-induced ovulation was used as a model to study the effect of drugs interfering with monoamine neurotransmission on CNS processes controlling ovulation. The drugs were administered during the critical period on day 32 and tubal eggs were counted in the morning of day 33. When injected during the critical period, dopamine (DA) receptor agonists such as apomorphine, ET 495, ergotamine, 2-bromo-α-ergocryptine, lergotrile and ergocornine inhibited ovulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Recently, it has been suggested that multiple hypothalamic DA systems may be controlling LH release with the TIDA or A12 neurons being inhibitory (and, perhaps stimulatory at higher doses) while the incertohypothalamic or AI3 DA system may be stimulatory to gonadotrophin release [3,[12][13][14][15][16][17], An involvement of the incertohypothalamic A 13 system in LH release was first demonstrated by Wikes et al [16] who showed that lesions of the zona incerta resulted in decreased levels of LHRH in the median eminence. This suggests that A13 DA neurons may be involved in the regulation of LHRH syn thesis or its release from LHRH terminals in the median emi nence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that multiple hypothalamic DA systems may be controlling LH release with the TIDA or A12 neurons being inhibitory (and, perhaps stimulatory at higher doses) while the incertohypothalamic or AI3 DA system may be stimulatory to gonadotrophin release [3,[12][13][14][15][16][17], An involvement of the incertohypothalamic A 13 system in LH release was first demonstrated by Wikes et al [16] who showed that lesions of the zona incerta resulted in decreased levels of LHRH in the median eminence. This suggests that A13 DA neurons may be involved in the regulation of LHRH syn thesis or its release from LHRH terminals in the median emi nence.…”
Section: Discussionmentioning
confidence: 99%
“…However, of these three schemes, 3 is the most compelling (Fink, 1988 a, b) here. First, the inhibitory action of dopamine on LHRH-LH release was first suggested by Fuxe & H6kfelt (1970) and later by Lofstr6m, Agnati, Fuxe & H6kfelt (1977) on the basis of measurement of catecholamine turnover in the median eminence. These findings are supported by direct evidence from our studies in which we investigated the effect of pharmacological manipulation of catecholamines on the LHRH surge induced in immature rats by administering pregnant mare serum gonadotrophin (PMSG).…”
Section: Rapid Effects Of Steroidsmentioning
confidence: 99%
“…Furthermore, upon TH inhibition a clearly significant lowering of LH serum levels was also demonstrated in these nicotine-treated female rats. These results may be explained on the basis of an increased dependency on release of CA from adrenaline and NA nerve terminal systems of the hypothalamus and preoptic area known to have a stimulatory role in the control of serum TSH and LH levels (12,(18)(19)(20)(21)(22)(23)(24). This increase in the dependency of stimulatory NA and adrenaline networks may be related to the increase in DA utilization in the tubero-infundibular DA neurons, which exhibit inhibitory effects on serum TSH, prolactin and LH levels.…”
Section: Discussionmentioning
confidence: 99%